Learning Process of Effectiveness Enhancement of Mushroom Production with Appropriate Technology on Area-based Agriculture : Case study of innovation community “Na-Wat-Takam Farm Mee Sook” Mae Suk Subdistrict, Jae Hom District, Lampang Province - changjeraja, sunti; changjeraja, rungnapa; Nualboonreang, Pongyuth; Amthong, Siriporn (RMUTL Journal of Socially Engaged Scholarship, 2024)
Learning process of effectiveness enhancement of mushroom production with appropriate technology on area-based agriculture : case study of innovation community “Na-Wat-Takam Farm Mee Sook” Mae Suk Subdistrict, Jae Hom District, Lampang Province. The objective is to create appropriate knowledge/technology process products, create learning spaces and have community innovators with knowledge and ability to expand the results to sustainable career development. There is a development of a model/form of creating an innovative community to participate in upgrading the agricultural way of life of the Mae Suk mushroom growing group. The participation mechanism to enhance the development of the Mae Suk mushroom cultivation group using the original capital as a base has set the steps for 4 activities as follows: Activity 1: Develop participatory learning group processes, organize a meeting to clarify and create understanding of research operations and create a participatory process for the “research network”, jointly operate focus groups, create values for the network group, analyze and examine problem data that is consistent with the real needs of the community, enhance skills and knowledge in the participatory research process. Activity 2: The process of collecting and researching spatial data and issues, with a mechanism for conducting surveys, collecting spatial data, and studying the mushroom production process, analyzing details of the learning base, and developing the production process using production questionnaires. Activity 3: Mechanism for cultivating community researchers/community innovators in production systems and production management that are efficient and low cost in the community, creating a participatory action research (PAR) learning process between the research team in the project and the community research team, training workshops, and cultivating community researchers together with academics, planning production, jointly determining and designing learning approaches to develop innovations or the use of appropriate technology for actual experimentation in production areas, comparing with the original production models of community researchers. And activity 4: Data collection: Measure the knowledge of the community research team before and after the research operation using questionnaires, interviews, satisfaction with the operation of various activities and the overall operation. Analyze and classify changes in the original capital base to produce results according to the innovation community goals in 4 components: 1) Learning Exchange Area 1 Learning Prototype "At-Wat-Takam Farm Meesuk" Mae Suk Subdistrict, Chae Hom District, Lampang Province, which has components of home, temple, school (vocational development learning model) with the temple as the center of learning, can be linked to the policy area development plan of Lampang Province. 2) Learning activities to enhance learning skills in the mushroom production value chain, such as training, incubation, study tours, knowledge exchange within and outside the community, or expanding into online networks, focusing on learning groups of elderly people in the community to form career groups and generate income for themselves and their families. 3) Ready-to-use knowledge or innovation: There is a set of appropriate technological knowledge that can be expanded to manage the value chain, including mushroom houses, simple automatic watering systems in mushroom houses that can be linked to the management of mushroom production with safe quality standards, and processing to add value to mushrooms. And 4) Community innovators: There were 9 community innovators in Ban Mae Suk community who developed from their experiences, which can be measured by their abilities, efforts, and attitudes in accepting, adapting, and expanding the knowledge and experiences to community members and interested people so that they can apply them in practice.